Co-Doping Effects in CdWO4 Scintillator Thin Films as Alpha Counters: Ag and Gd Cases - Nooshin Heydarian Dehkordi; Morteza Raeisi; Sanaz Alamdari (Nanochemistry Research)
The flexible CdWO4 (CWO)-20 wt. % polyester (PES) and CWO: 0.5 at. % Ag, 0.5 at. % Gd (co-doped CWO)-20 wt. % PES thin films were prepared by direct mixing technique. The composition of thin films was studied by EDAX analysis. FE-SEM and EDAX-map images exhibited a uniform distribution of CWO and co-doped CWO nanoparticles (NPs) in PES. The precision of the Monte Carlo technique for the computation of alpha particle trajectories in CWO-20wt. % PES and co-doped CWO-20wt. % PES thin films were 55 and 53 µm, respectively, which approximately agreed with FE-SEM images. The band gap energy of co-doped CWO increased based on DRS results. The scintillation responses of thin films were investigated using a 241Am source. Co-doping increased the absolute counting efficiency (up to 74%) and decreased the energy resolution (up to 39 %). The mechanical properties, transparency, and gloss of nanocomposites were also investigated. The results indicate that the manufactured nanocomposites could be promising candidates for ionizing radiation detectors, radiometric monitoring, and light-emitting diodes (LEDs).